Behaviours of the lattice-polarity inversion in AlN growth on c-Al2O3 (0001) substrates by ammonia-free high temperature metalorganic chemical vapor deposition. Issue 33 (3rd August 2022) - Shen, Xuqiang; Matsuhata, Hirofumi; Kojima, Kazutoshi
Abstract : A BF-STEM image and inserted magnified HR-HAADF-STEM images showing the different lattice-polarity of AlN at each position. Abstract : We experimentally investigate the microstructures and growth features of AlN epilayers on c-Al2 O3 (0001) substrates grown by ammonia-free high-temperature metalorganic chemical vapor deposition (AFHT-MOCVD). Besides the conventional threading dislocations (TDs) in the AlN epilayer and the voids at the AlN epilayer/substrate interface, a lattice-polarity inversion phenomenon is confirmed in the AlN growth, where a laterally distributed zigzag inversion domain boundary (IDB) is observed. Lattice-polarity at different points in the AlN epilayer is directly determined with a high-resolution scanning transmission electron microscope (HR-STEM). A series of AlN morphological characterizations by scanning electron microscope (SEM) with and w/o KOH etching faithfully reproduces the lattice-polarity inversion process at the different AlN growth stages. An AlN micro-crystal with N-polarity is first grown on the sapphire substrate. Then the lattice-polarity inversion process begins to appear here and there with the formation of small Al-polar AlN trapezoids. With the growth in progress, an IDB formation with a laterally distributed zigzag shape is achieved due to the higher growth rates in Al-polar AlN both in the vertical and lateral directions. Finally, the initially grown N-polar AlN is completely covered by the Al-polar AlN, resulting in a pure Al-polar AlN epilayer on the top. Our results in this study give deep insights into the mechanism behind the unique growth technique for high-quality AlN growth, which is important for optical and electronic device applications.